Acoustophoretic separation of infected erythrocytes from blood plasma in a microfluidic platform using biofunctionalized, matched‐impedance layers. (27th December 2017) - Gupta, Tamaghna; Ghosh, Ritwick; Ganguly, Ranjan
Abstract: Acoustophoresis is rapidly gaining prominence in the field of cell manipulation. In recent years, researchers have extensively used this method for separating different types of cells from the bulk fluid. In this paper, we propose a novel acoustophoresis‐based technique to capture infected or abnormal erythrocytes from blood plasma. A typical acoustic device consisting of a transducer assembly, microfluidic cavity, and a reflector is considered. Based on the concept of impedance matching, a pair of antibody‐coated polystyrene layers is placed in the nodal regions of an acoustic field within the cavity. This technique allows bi‐directional migration of the suspended cells to the biofunctionalized surfaces. Therefore, simultaneous capture of infected erythrocytes on both the layers is feasible. Finite element method is used to model the pressure field as well as the motion of erythrocytes under the influence of acoustic radiation, drag, and gravitational forces. A parametric analysis is done by varying the excitation frequency, driving voltage, and the thickness of the polystyrene layers. The resulting changes in the pressure amplitude and field pattern are investigated. The erythrocyte collection efficiency, rate of collection, and the cell distribution on the layer surfaces are also determined under different field conditions. The occurrence of transient cavitation in the blood plasma‐filled cavity at the chosen frequency is taken into account by using its threshold pressure value as the limiting factor of pressure amplitude. The study provides an insight into the phenomenon and serves as a guideline to fabricate low‐cost, multifunctional rapid diagnostic devices based on acoustophoretic separation. Abstract : We present a novel technique to capture infected cells from blood plasma on thin biofunctionalized polystyrene layers based on acoustophoretic cell manipulation and the concept of matched impedance. The effects of key process parameters like excitation frequency, driving voltage, and layer thickness on acoustophoresis of cells are studied. This simulation work is in good agreement with a previously reported experimental study of particle separation in a fluid medium.